Strategi Kepala Sekolah Memaksimalkan Mutu Pendidikan di SMP Negeri 1 Air Salek - Budi Raharjo; Dessy Wardiah; Destiniar Destiniar (Mathematics Education Study Program, 2025)
This study aims to determine and describe the planning, implementation and evaluation of the principal in maximizing the quality of education at SMP Negeri 1 Air Salek The method used is a qualitative method. Data collection techniques use observation, interviews and documentation. The results of the study can be concluded that the Principal's Strategy in Improving the Quality of Education at SMP Negeri 1 Air Salek is through enforcing discipline, being responsible for the tasks given to both teachers and principals. The principal in improving the quality of education is highly prioritized. Various strategies have been carried out, including the first one, such as implementing school-based management to encourage direct participation so that in making decisions it is more responsive and involving parents through committees so that parents know the quality of the school, and working together with other institutions so that education is more optimal, improving the development of teacher quality through seminars and sending training held by the district office to improve teacher quality.